2019
DOI: 10.1177/0886260519852160
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Relational Adverse Childhood Experiences on Suicide Outcomes During Early and Young Adulthood

Abstract: This study aimed at investigating the degree to which relational adverse childhood experiences (ACEs) would affect suicide outcomes during early and young adulthood of Iranian female and male students. In all, 487 undergraduate students (59.2% females) with a mean age of 20.66 ± 1.42 were recruited using a multistage clustering sampling method from eight schools from the fields of humanities, engineering, and basic sciences. Suicide Behavior Questionnaire–Revised form (SBQ-R) was employed for assessing past ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Additionally, the odds of adult survivors experiencing serious depression are more than twice the general population. Adult survivors of CM are also 12 times more likely to commit suicide (Felitti et al, 1998; Pournaghash-Tehrani, Zamanian, & Amini-Tehrani, 2019; Salokangas et al, 2019). Those who experienced CM were also significantly more likely to perpetrate CM, criminal violence, and intimate partner violence (Milaniak & Widom, 2015; Oliver, 1993).…”
mentioning
confidence: 99%
“…Additionally, the odds of adult survivors experiencing serious depression are more than twice the general population. Adult survivors of CM are also 12 times more likely to commit suicide (Felitti et al, 1998; Pournaghash-Tehrani, Zamanian, & Amini-Tehrani, 2019; Salokangas et al, 2019). Those who experienced CM were also significantly more likely to perpetrate CM, criminal violence, and intimate partner violence (Milaniak & Widom, 2015; Oliver, 1993).…”
mentioning
confidence: 99%
“…Currently, there is a lack of research on gender differences in the association between ACEs and HRB patterns. However, some scholars have attempted to identify gender differences between ACEs and a single risky behavior [ 24 , 25 ]. The overall results have not been uniform; for example, a national urban birth cohort study assessed that girls were more likely to develop externalizing behavioral problems after exposure to adversity, compared to boys [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Socialization of gender differentiation may enable boys to gain more autonomy and freedom to spend time outside, thus giving boys more opportunities to engage in risky behavior than girls. In addition, studies suggest that the gender differences between ACEs and risk behaviors are uncertain in adolescents [ 24 , 25 ]. Therefore, different socio-cultural contexts may lead to gender differences in the association between ACEs and HRBs patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has confirmed a dose-response association between ACE scores and an array of health problems across the lifespan (e.g., Anda et al, 2006;Dong et al, 2003). Recent investigations of the ACE questionnaire have provided empirical support for expanding the content, including additional adverse events such as unsafe neighborhoods and perceived discrimination (Cronholm et al, 2015), peer victimization (Finkelhor et al, 2015;Pournaghash-Tehrani et al, 2019), and maltreatment by school authorities (Pournaghash-Tehrani et al, 2019). In addition, global organizations, such as the World Health Organization (WHO), are working through validation trials on a revised version of the ACE International Questionnaire (ACE-IQ;World Health Organization, 2018).…”
Section: Adverse Childhood Experiences Questionnairementioning
confidence: 99%